Periventricular Location as a Risk Factor for Hemorrhage and Severe Clinical Presentation in Pediatric Patients with Untreated Brain Arteriovenous Malformations - Ma, L. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: The morphologic features of brain arteriovenous malformations differ between children and adults; therefore, our aim was to analyze various features of brain arteriovenous malformations to assess the risk of hemorrhage in children. MATERIALS AND METHODS: We identified all consecutive children admitted to Beijing Tiantan Hospital for brain arteriovenous malformations between July 2009 and April 2014. The effects of demographic characteristics and brain arteriovenous malformation morphology on hemorrhage presentation, annual bleeding rates, postnatal hemorrhage, and immediate posthemorrhagic neurologic outcomes were studied by using univariate and multivariable regression analyses. RESULTS: A total of 108 pediatric brain arteriovenous malformation cases were identified, 66 (61.1%) of which presented with hemorrhage. Of these, 69.7% of ruptured brain arteriovenous malformations were in a periventricular location. Periventricular nidus location (OR, 3.443; 95% CI, 1.328–8.926; P = .011) and nidus size (OR, 0.965; 95% CI, 0.941–0.989; P = .005) were independent predictors of hemorrhagic presentation. The annual hemorrhage rates in children with periventricular brain arteriovenous malformations were higher at 6.88% (OR, 1.965; 95% CI, 1.155–3.341; P < .05). The hemorrhage-free survival rates were also lower for children with periventricular brain arteriovenous malformations (log-rank, P = .01). Periventricular location (hazard ratio, 1.917; 95% CI, 1.131–3.250; P = .016) and nidus size (hazard ratio, 0.983; 95% CI, 0.969–0.997; P = .015) were associated with hemorrhage after birth in pediatric brain arteriovenous malformations. An ordinal analysis showed lower immediate posthemorrhage mRS in patients with periventricular brain arteriovenous malformations (OR for greater disability, 2.71; 95% CI, 1.03–7.11; P = .043). CONCLUSIONS: Small periventricular brain arteriovenous malformations were associated with increased hemorrhage risk in pediatric patients. Cautious follow-up of children with untreated periventricular brain arteriovenous malformations is recommended because of a higher hemorrhage risk and potentially more severe neurologic outcomes.